Alcoholism in women treated at Clinic for Psychiatry - research of selected factors - Milan Stojaković; Sanja Vukadinović (Биомедицинска истраживања, 2010)
Introduction: Drinking alcoholic beverages and the problems associated with excessive drinking have always been much more common in men than in women. However, alcoholism in women has recently become a growing problem. It is believed that the number of women alcoholics is growing faster than the overall increase in the number of alcoholics. The aim of the study was to find out the prevalence of alcohol use disorders in women treated at the Psychiatric Clinic in Banja Luka, and to find out some factors (attitude toward alcoholism, age, sex, marital status, education level, place of living, type of beverage, additional psychiatric disorders) that have an impact on the very prevalence of the disease. Methods: The data from medical records of patients treated at the Department of Psychiatry, Clinical Center Banja Luka, PTSS test and HAMD were used. The specifically designed surveys for adults were used as data sources. Results: Out of 200 hospitalized female patients 45% of respondents occasionally drank alcohol prior to admission, 31% of them answered that they did not drink at all, 18.5% of them have tried alcohol and 5.5% of them answered that they consumed alcoholic beverages every day. The ratio between women and men treated for alcohol use disorders during the study was 1:5.03. Conclusion: The study included a greater number of highly educated women (55.5%) than non-educated ones (44.5%). Unmarried women drink most (39%), then divorced or women in divorce proceedings (30%), married women (25%) and widows (6%). 56% of women who drink alcohol live in urban areas whereas 44% of them live in rural areas. Women more often drink stiff drinks (67%), and they have more additional depressive disturbances or depressive disorder (69.5%) than other psychiatric disorders. Our research shows that the ratio between women and men treated for alcoholism at the Department of Psychiatry is 1:5.03.
Keywords: alcoholism; women; factors of disease prevalence